2018
DOI: 10.1093/jas/sky327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary pectin on the profile and transport of intestinal bile acids in young pigs

Abstract: Pectin has been known to lower circulating cholesterol by interacting with bile acid (BA) metabolism. The current study was aimed to investigate intestinal BA transport at the molecular level in a pig model. Twelve young pigs (11.05 ± 0.11 kg) were randomly divided into 2 groups and fed corn-soybean meal diets with either 5% pectin or cornstarch for 72 d. In pigs fed with pectin, total cholesterol and low-density lipoprotein cholesterol (LDL-C) were lowered but high-density lipoprotein (HDL-C) was increased (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 35 publications
2
25
1
Order By: Relevance
“…Increasing concentrations of HDL are strongly associated with decreasing accumulation of atherosclerotic plaques within walls of arteries [39]. Conversely, LDL transports cholesterol from the liver to tissues of the body, and can be oxidized into low-density lipoprotein [40]. Herbs such as Portulaca oleracea reduces triglyceridemia, cholesterolemia, and improves reverse cholesterol transport in rats [41], Gatreh-Samani [42] showed that serum TC, TG and LDL decreased and HDL increased in patients who received 50 or 60 g of Portulaca oleracea per day.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing concentrations of HDL are strongly associated with decreasing accumulation of atherosclerotic plaques within walls of arteries [39]. Conversely, LDL transports cholesterol from the liver to tissues of the body, and can be oxidized into low-density lipoprotein [40]. Herbs such as Portulaca oleracea reduces triglyceridemia, cholesterolemia, and improves reverse cholesterol transport in rats [41], Gatreh-Samani [42] showed that serum TC, TG and LDL decreased and HDL increased in patients who received 50 or 60 g of Portulaca oleracea per day.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, about 100 mg of feces were ultrasonic extracted with 1 mL of methanol. The methanol extracts obtained were filtered and analyzed by LC‐MS/MS approach as previous described 32 . BAs were identified by comparison with the retention time of standard substance.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed experimental design and animals are described in Fang et al [19], and intestinal samples used in the present study were obtained from the same pigs. Briefly, twelve Duroc × Large White crossbred piglets (initial body weight: 11.05 (SD 0.11) kg) were randomly assigned to one of two diets, in a randomized design.…”
Section: Experimental Design and Animalsmentioning
confidence: 99%
“…PEC is found to stimulate growth and activity of bacterial genera, such as Prevotella, Lactobacillus and Faecalibacterium [15][16][17], members of which have been shown to promote gut health [15,18]. In pigs, we recently showed that PEC intake significantly affected ileal and cecal secondary bile acids metabolism, which was closely related to changes in the intestinal microbiota and may have consequences for microbe-host signaling [19]. Many studies have investigated PEC-related alteration in luminal or fecal microbiota; however, we previously showed that alteration of mucosal associated microbiome may be a very important mechanism of PEC effect on immune function [20].…”
Section: Introductionmentioning
confidence: 99%